Enhancing Local Tax Governance through Regulatory Impact Assessment (RIA): A Study on Edible Bird’s Nest Tax Regulation in Kolaka Regency, Indonesia - Rahmad Hidayat; Patma Sari; La ode Awal Sakti; Rosnida Rosnida; Irabiah Irabiah; Yeni Haerani; Lisma Lisma (Al-Adalah: Jurnal Hukum dan Politik Islam, 2025)
This study examines the application of the Regulatory Impact Assessment (RIA) methodology in the formulation of local tax regulations, using the edible bird’s nest (EBN) tax policy in Kolaka Regency, Indonesia, as a case study. Despite the region’s significant fiscal potential from EBN, the 2024 Regional Regulation on EBN taxation was enacted without a formal impact assessment, resulting in policy shortcomings such as low compliance, weak stakeholder engagement, and minimal revenue realization. Employing a normative-empirical legal research method, this study integrates statutory analysis with qualitative data collected through interviews with government officials, parliamentarians, and EBN producers. Findings reveal a mismatch between the legal design and the socio-economic realities on the ground, underscoring the absence of behavioral insights, participatory mechanisms, and implementation planning. The study argues that institutionalizing RIA in subnational governance can enhance regulatory legitimacy, transparency, and policy effectiveness, particularly in resource-based rural economies. It concludes by recommending the adoption of RIA as a standard practice in regional tax lawmaking, supported by capacity-building and inclusive stakeholder processe.